Suomen metsäteollisuudennäkymiä vuoteen 2025 - Birgitta Berg-Andersson; Ville Kaitila; Martti Kulvik; Jussi Lintunen (The Research Institute of the Finnish Economy (ETLA), 2021)
– The importance of our forests is growing. Forest industry has retained its vital position within Finnish economy, and it seems reasonable to assume our forests' value added will contribute to Finland's wealth also far into the future. Of more recent interest is the value of forests being Finland's major carbon sink. This report discusses the past, present and future of the Finnish forest sector acknowledging both economic and environmental aspects. In the first part, we describe the impacts of the forest industry sectors to Finnish economy in large. National accounts input-output statistics show that the forest industries use significant shares of domestic intermediate products, and hence they connect extensively to other industry sectors. The second section looks at recent development as well as prospects up to year 2025. We expect wood industry to recover rather quickly from the backlash triggered by the COVID-19 pandemic, but paper and pulp industry to experience a less favourable development - particularly due to the fast decrease in demands of paper. The third and final contribution assesses quantitatively how logging relates to the carbon sink of Finnish forests. Our novel model suggests total roundwood removals to have a rather strong impact on forest land carbon sink. We estimate Finland's carbon sink to increase due to COVID-19 perturbed drop in logging, and the sink increase to remain relatively strong during the next few years.
Keywords: L69; L73; Q23; Q54; D57; 330; Finnish forest sector; Near future; Economic forecast